2019
DOI: 10.1101/843110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microtubule Nucleation Promoters Mto1 and Mto2 Regulate Cytokinesis in Fission Yeast

Abstract: Dundon and Pollard show that compromising the Mto1 or Mto2 regulators of the fission yeast γtubulin complex reduces or eliminates astral microtubules, exaggerates the effects of a non-lethal D277N substitution in β-glucan synthase 1 (Cps1/Bgs1) on the rate of cytokinetic furrow formation, and increases Rho-GTP at the cleavage site. AbstractMicrotubules of the mitotic spindle direct cytokinesis in metazoans but this has not been documented in fungi. We report evidence that astral microtubules help coordinate cy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…To test if the turgor pressure inhibited ring contraction in cps1-191 mutants, we cultured cps1-191 cells in EMMA medium containing 0.8 M sorbitol to decrease the turgor pressure to that inside the cells at the restrictive temperature, and we added 2-deoxyglucose (2-DG) to this culture to prevent further glucan synthesis at the division site and elsewhere in the cells (Megnet, 1965;Svoboda and Smith, 1972;Osumi et al, 1998). A recent study showed that rings in cps1-191 mutant cells constricted slowly after shifting to the restrictive temperature for ∼2 h before microscopy at the restrictive temperature (Dundon and Pollard, 2020). To ensure a highly penetrant phenotype for cps1-191, we shifted the cps1-191 cells to the restrictive temperature for ∼6 h before microscopy, which was performed at the restrictive temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test if the turgor pressure inhibited ring contraction in cps1-191 mutants, we cultured cps1-191 cells in EMMA medium containing 0.8 M sorbitol to decrease the turgor pressure to that inside the cells at the restrictive temperature, and we added 2-deoxyglucose (2-DG) to this culture to prevent further glucan synthesis at the division site and elsewhere in the cells (Megnet, 1965;Svoboda and Smith, 1972;Osumi et al, 1998). A recent study showed that rings in cps1-191 mutant cells constricted slowly after shifting to the restrictive temperature for ∼2 h before microscopy at the restrictive temperature (Dundon and Pollard, 2020). To ensure a highly penetrant phenotype for cps1-191, we shifted the cps1-191 cells to the restrictive temperature for ∼6 h before microscopy, which was performed at the restrictive temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The miscoordination of cytofission and nuclear division spatially could arise from the variable dumbbell-shaped morphology of cps1-191 spheroplasts (Mishra et al, 2012). The functions of Mto1 and Mto2, which are involved in the assembly of postanaphase microtubule arrays, may also contribute to these miscoordination defects (Dundon and Pollard, 2020). Because the cps1-191 mutant spheroplast division was morphologically different from normal fission yeast cell division and was mimicking the morphological changes of some animal cells during division, we have called this type of division cytofission.…”
Section: Resultsmentioning
confidence: 99%